Before and After: Digital story telling with social work students in Northern Ireland - MacDermott, Denise; Harkin-MacDermott, Caoimhe; Wylie, Siobhan (The Journal of Practice Teaching and Learning, 2019)
Abstract: This article is developed from a presentation given at the 12th International practice teaching conference in Oxford (2018). The authors share their experiences as academics and practice educators of using digital storytelling with social work students in Northern Ireland. Storytelling took place at two distinct points of the students’ learning journey before and after placement. Undergraduate social work students (n=40) in their first semester of year one teaching participated in classroom based digital storytelling with the first author. Placement students created digital stories at two key points during their placements, at the beginning (first to third week of placement) and at the end (16th to 18th week of placement). Several themes emerged including; self-evaluation and reflection, producing and receiving feedback and team work. This collaborative article offers a basis for practice development and professional discussions across disciplines on the use of digital storytelling with students studying for a professional qualification.